SIPA1 boosts migration and proliferation, and blocks apoptosis of glioma by activating the phosphorylation of the FAK signaling pathway - Du, Yuan; Li, Shenglan; Zhou, Tong; Zhao, Jing; Liu, Jiguang (Journal of Medical Biochemistry, 2021)
Background: We aimed to analyze the regulatory effects of SIPA1 (signal-induced proliferation-associated protein 1) on glioma progression and the dominant signaling pathway.Methods: Differential level of SIPA1 in glioma and normal tissues and cells was determined. Migratory, proliferative, apoptotic and cell cycle progression changes in A172 cells with overexpression or knockdown of SIPA1 were examined. Finally, protein levels of phosphorylated FAKs in A172 cells intervened by SIPA1 and the FAK inhibitor PF-562271 were detected.Results: SIPA1 was upregulated in glioma cases. Knockdown of SIPA1 reduced migratory and proliferative rates of glioma cells, increased apoptotic cell rate, and declined cell ratio in S phase. Cell cycle proteins were also downregulated by knockdown of SIPA1. SIPA1 upregulated phosphorylated FAKs in A172 cells and thus boosted malignant phenotypes of glioma.Conclusions: SIPA1 is upregulated in glioma that boosts migratory and proliferative potentials of glioma cells by activating the phosphorylation of the FAK signaling pathway.
Keywords: SIPA1; FAK; Phosphorylation; Glioma